Diabetes Care in the Philippines - Gerry H. Tan (2016)
BackgroundDiabetes is increasing at an alarming rate in Asian countries including the Philippines. Both the prevalence and incidence of type 2 diabetes (T2D) continue to increase with a commensurate upward trend in the prevalence of prediabetes.ObjectivesThe aim of this study was to review the prevalence of diabetes in the Philippines and to describe extensively the characteristics of diabetes care in the Philippines from availability of diagnostics tests to the procurement of medications.MethodsA literature search was performed using the search words diabetes care and Philippines. Articles that were retrieved were reviewed for relevance and then synthesized to highlight key features.FindingsThe prevalence of diabetes in the Philippines is increasing. Rapid urbanization with increasing dependence on electronic gadgets and sedentary lifestyle contribute significantly to this epidemic. Diabetes care in the Philippines is disadvantaged and challenged with respect to resources, government support, and economics. The national insurance system does not cover comprehensive diabetes care in a preventive model and private insurance companies only offer limited diabetes coverage. Thus, most patients rely on “out-of-pocket” expenses, namely, laboratory procedures and daily medications. Consequently, poor pharmacotherapy adherence impairs prevention of complications. Moreover, behavioral modifications are difficult due to cultural preferences for a traditional diet of refined sugar, including white rice and bread.ConclusionsTranslating clinical data into practice in the Philippines will require fundamental and transformative changes that increase diabetes awareness, emphasize lifestyle change while respecting cultural preferences, and promote public policy especially regarding the health insurance system to improve overall diabetes care and outcomes.